Розрахунок електричного поля в плівковій діелектричній системі як спосіб прогнозування електричної міцності високовольтного імпульсного конденсатора - Дмитрішин, Олексій Ярославович (НТУ "ХПІ", 2018)
Розглянуто питання визначення напруженості електричного поля в плівковій діелектричній системі, яка може бути використана у якості робочого діелектрика секції високовольтного імпульсного конденсатора. Досліджено вплив напруженості електричного поля на електричну міцність комбінованої плівкової діелектричної системи. Проведено порівняння розрахункових даних з експериментальними, на основі якого зроблені виводи о можливості прогнозування електричної міцності плівкових діелектричних систем.

The problems of determining the electric field strength in a film dielectric system, which can be used as a working dielectric in the section of a high-voltage pulse capacitor, are considered. The effect of the density of electric field on the electrical strength of a combined film dielectric system is studied. Methods of solution of the Laplace equation and of conformal mappings are used for calculations. Comparison of calculated data with experimental data, on the basis of which conclusions are made about the possibility of predicting the electrical strength of film dielectric systems, is made. It’s shown that for combined film dielectric systems of the same qualitative composition, the geometric dimensions and the coefficient of heterogeneity affects the electrical strength more than the distribution of the electric field intensity on the components of this system.
Calculation of the electric field in a film dielectric system as a method for predicting the electrical strength of a high-voltage pulse capacitor
Keywords: напруженість електричного поля; робочий діелектрик; секція конденсатора.; розрахунок напруженості; density of electric field; film dielectric system; dielectric strength